Psychological, social and behavioural factors associated with disease/illness activity and adjustment to Lupus: A systematic review and meta-analysis - Silva-Ribeiro, S.; Godinho, C. A.; Camilo, C.; Marques, M. M.; Chisari, C.; Segura, U.; Bernardes, S. F. (Health Psychology Review, 2025)
Systemic Lupus Erythematosus (SLE) bears a heavy toll on individuals’ psychological wellbeing and quality of life. Despite vital to the development of effective interventions, systematic and quantifiable knowledge on modifiable factors associated with adult SLE adjustment and disease/illness activity is currently lacking. This systematic review with meta-analysis aimed to bridge this gap, by examining the effects of modifiable psychological, social, and behavioural factors associated with SLE adjustment and disease/illness activity. Eight databases were searched for quantitative studies, using Boolean combinations of keywords on SLE adjustment, disease/illness activity and psychological, social, or behavioural correlates/predictors. Ninety studies were included in the narrative review, and fifty-four in the meta-analysis. The psychological factors more strongly associated with SLE adjustment and disease/illness activity were illness– and treatment-related illness- and treatment-related beliefs, self-perceptions, resilience-related factors, and perceived stress. Avoiding sedentary behaviour showed a consistent, albeit small association with better outcomes. Social factors were largely under investigated, but better perceived social support showed moderate associations with better outcomes. The meta-analysis findings, which should be considered with caution due to high risk of bias, uncovered several potentially fruitful avenues for future research and highlight potentially relevant targets for psychosocial and behavioural interventions to improve quality of life of individuals with SLE.